Shifting epidemic trends and severity in pediatric Mycoplasma pneumoniae infections in the post-COVID-19 era - Yang, Zongming; Shi, Rui; Zhou, Xiuyun; Xu, Dong; Xue, Wankai; Zhang, Wenjing; Cao, Xiaopei; Peng, Jing; Luo, Xiaoping; Huang, Yongjian (Italian journal of pediatrics, 2025)
While non-pharmaceutical interventions (NPIs) implemented for COVID-19 have been shown to affect the epidemiology of respiratory pathogens, the impact of China's prolonged NPIs on Mycoplasma pneumoniae (MP) remains unclear. This study aimed to analyze the MP test positivity rates, as well as assessing disease severity in pediatric cases before and after the three-year NPI period. We conducted a repeated cross-sectional study using electronic health records from Tongji Hospital, Wuhan, China. Children aged ≤ 14 years who tested nasopharyngeal/oropharyngeal swabs for MP using real-time polymerase chain reaction from January 2023 to June 2024 were included, along with data from four pre-intervention years (2016-2019). Primary outcomes included monthly MP test positivity rates and severity outcomes. To assess changes in test positivity, segmented quasi-Poisson regression models were used to calculate prevalence ratio (PR) and 95% confidence interval (CI). Linear regression models were employed to evaluate changes in continuous severity parameters, while log-binomial models were used to assess the PR for dichotomous severity outcomes. Among 56,232 pediatric patients, 10,476 (18.63%) tested positive for MP. The post-intervention MP resurgence peaked later, with an average monthly positivity rate significantly exceeding predicted values (18.77% vs. 10.87%; PR = 1.69, 95% CI: 1.33, 2.16). After adjusting for age and sex, children hospitalized with MP infection in the post-intervention period exhibited higher white blood cell counts (10^ /L, β = 0.60, 95% CI: 0.24, 0.97), lower lactate dehydrogenase levels (IU/L, β=-11.15 95% CI: -18.76, -3.55), lower hemoglobin levels (g/L, β=-1.44, 95% CI: -2.05, -0.83), and increased risks for bronchopneumonia (PR = 1.35, 95% CI: 1.02, 1.81), oxygen administration (PR = 3.95, 95% CI: 3.32, 4.76), intrapulmonary complications (PR = 2.73, 95% CI: 2.03, 3.76), extrapulmonary complications (PR = 1.76, 95% CI: 1.41, 2.22), severe pneumonia (PR = 1.45, 95% CI: 1.22, 1.74), and glucocorticoid use (PR = 1.17, 95% CI: 1.11, 1.25) compared with the pre-intervention group. A significant increase in MP infections and disease severity was observed following the relaxation of NPIs in late 2022, warranting further investigation into the long-term effects of NPIs on MP infections in children.